Reduced DNA methylation patterning and transcriptional connectivity define human skin aging. Issue 3 (23rd March 2016) - Bormann, Felix; Rodríguez‐Paredes, Manuel; Hagemann, Sabine; Manchanda, Himanshu; Kristof, Boris; Gutekunst, Julian; Raddatz, Günter; Haas, Rainer; Terstegen, Lara; Wenck, Horst; Kaderali, Lars; Winnefeld, Marc; et al.
Summary: Epigenetic changes represent an attractive mechanism for understanding the phenotypic changes associated with human aging. Age‐related changes in DNA methylation at the genome scale have been termed 'epigenetic drift', but the defining features of this phenomenon remain to be established. Human epidermis represents an excellent model for understanding age‐related epigenetic changes because of its substantial cell‐type homogeneity and its well‐known age‐related phenotype. We have now generated and analyzed the currently largest set of human epidermis methylomes ( N  = 108) using array‐based profiling of 450 000 methylation marks in various age groups. Data analysis confirmed that age‐related methylation differences are locally restricted and characterized by relatively small effect sizes. Nevertheless, methylation data could be used to predict the chronological age of sample donors with high accuracy. We also identified discontinuous methylation changes as a novel feature of the aging methylome. Finally, our analysis uncovered an age‐related erosion of DNA methylation patterns that is characterized by a reduced dynamic range and increased heterogeneity of global methylation patterns. These changes in methylation variability were accompanied by a reduced connectivity of transcriptional networks. Our findings thus define the loss of epigenetic regulatory fidelity as a key feature of the aging epigenome.